Evaluasi Pengelolaan Sampah di Rumah Sakit Umum Daerah (RSUD) Hadji Boejasin Pelaihari Kabupaten Tanah Laut Kalimantan Selatan - Fadhilah Rahman; Sarto Sarto; Susi Iravati (Center for Health Policy and Management, 2017)
ABSTRACTBackground: The hospital was a health-care facility for public services, a gathering place for sick people or healthy people who allowed environmental pollution, health problems or may be spread of disease transmissions. The existence of health care facilities also can have negative impacts on the environment and surrounding communities, especially when the waste/garbage service facilities was not maintained properly. According to the annual report of the General Hospital of Hadji Boejasin Pelaihari in 2010, the number of patients has increased significantly which will also affect the amount of waste generated either medical waste or waste nonmedical.Objectives: To evaluate the existing waste management activities at the General Hospital of Hadji Boejasin Pelaihari.Methods: Descriptive research on qualitative and quantitative approach with the main objective to create an objective overview of waste management situation objectively. Data analysis was done by using annotations, all data/sources examined and evaluated together so that all of the findings in this study was combination of a different variety of information. Data analysis was performed by analysis of transcript questionnaires, followed by analysis of the observation checklist.Results: Waste management activities in the operational techniques were that phase segregation still existed on where medical waste contents mixed with a kind of other trash, garbage collected to inpatient, transporting medical waste and garbage nonmedical combined with three-wheel motorcycle to the polls, medical waste that was collected on the spot temporary shelter while nonmedical trash dumped into landfills. Cleaners who has not been trained about hospital waste management, as well as fixed procedures (SOP), did not exist in a guideline for the janitor on waste management.Conclusion:The waste management and disposal in General Hospital Hadji Boejasin has been in accordance with applicable regulations, so it required reformation to make better. Keywords: Pengelolaan sampah, RSUD ABSTRAKLatar Belakang: Rumah sakit merupakan sarana pelayanan kesehatan untuk pelayanan umum, tempat berkumpulnya orang sakit maupun orang sehat yang memungkinkan terjadinya pencemaran lingkungan, gangguan kesehatan atau dapat menjadi tempat penyebaran penularan penyakit. Adanya saranalayanan kesehatan juga dapat menimbulkan dampak negatif bagi lingkungan dan masyarakat sekitar, terutama bila limbah/ sampah sarana layanan tersebut tidak dikelola dengan benar. Peningkatan jumlah pasien di Rumah Sakit Umum Daerah Hadji Boejasin Pelaihari akan mempengaruhi jumlah timbulan sampah yang dihasilkan baik itu sampah medis maupun sampah nonmedis.Tujuan:Untuk mengevaluasi kegiatan pengelolaan sampah yang ada di Rumah Sakit Umum Daerah Hadji Boejasin Pelaihari.Metode: Jenis penelitian deskriptif dengan metode pendekatan kualitatif dan kuantitatif. Analisa data dilakukan dengan teknik penjelasan. Data dievaluasi disajikan dengan narasi maupun dalam bentuk tabel. Selanjutnya dianalisa untuk mengetahui sejauhmana kesesuaian antara keadaan seharusnya dengan kenyataan yang didapat pada pengelolaan sampah yang ada di RSUD Hadji Boejasin.Hasil Penelitian: Kegiatan pengelolaan sampah pada teknik operasional yaitu tahap pemilahan masih ada tempat sampah medis yang isinya bercampur dengan jenis sampah lain, sampah dikumpulkan diantara ruang rawat inap, pengangkutan sampah medis dan sampah nonmedis digabung dengan menggunakan kendaraan roda tiga ke TPS, sampah medis dikumpulkan pada tempat penampungan sementara sedangkan sampah nonmedis dibuang ke tempat pembuangan akhir. Tenaga kebersihan yang ada belum pernah dilatih tentang pengelolaan sampah rumah sakit,begitu juga dengan prosedur tetap (SOP) yang merupakan pedoman bagi petugas kebersihan dalam pengelolaan sampah belum ada.Kesimpulan: Pengelolaan dan penanganan sampah yang ada di RSUD. Hadji Booejasin secara umum masih belum sesuai dengan peraturan yang berlaku, sehingga masih perlu pembenahan yang lebih baik lagi. Kata kunci: Pengelolaan sampah, RSUD